Emended description of the genus Actinokineospora Hasegawa 1988 and transfer of Amycolatopsis fastidiosa Henssen et al. 1987 as Actinokineospora fastidiosa comb. nov. - Labeda, D.P.; Price, N.P.; Tan, G.Y.A.; Goodfellow, M.; Klenk, H.P. (Society for General Microbiology, 2010)
The species Amycolatopsis fastidiosa (ex Celmer et al. 1977) Henssen et al. 1987 was proposed, based on morphological and chemotaxonomic observations, for a strain originally described as `Pseudonocardia fastidiosa' Celmer et al. 1977 in a US patent. In the course of a phylogenetic study of the taxa with validly published names within the suborder Pseudonocardineae based on 16S rRNA gene sequences, it became apparent that this species was misplaced in the genus Amycolatopsis. After careful evaluation of the phylogeny, morphology, chemotaxonomy and physiology of the type strain, it was concluded that this strain represents a species of the genus Actinokineospora that is unable to produce motile spores. The description of the genus Actinokineospora is therefore emended to accommodate species that do not produce motile spores, and it is proposed that Amycolatopsis fastidiosa be transferred to the genus Actinokineospora as Actinokineospora fastidiosa comb. nov. The type strain is NRRL B-16697(T) =ATCC 31181(T) =DSM 43855(T) =JCM 3276(T) =NBRC 14105(T) =VKM Ac-1419(T).